Assessing fitness to drive in older adults: Validation and extension of an economical screening tool. (January 2021) - Schulz, Philipp; Beblo, Thomas; Spannhorst, Stefan; Boedeker, Sebastian; Kreisel, Stefan H.; Driessen, Martin; Labudda, Kirsten; Toepper, Max
Highlights: We validated a new instrument called Safety Advice For Elderly drivers (SAFE). The SAFE allows the screening of driving-related risk factors in older adults. The SAFE significantly differentiated between fit and unfit older drivers. The SAFE appears to be a cost-efficient and user-friendly screening tool. Including additional evidence-based risk factors clearly improved diagnostic accuracy. Abstract: Objectives: : Due to demographic change, the number of older drivers with impaired driving skills will increase in the next decades. The current study aimed at the validation and extension of the screening tool Safety Advice For Elderly drivers (SAFE) that allows a cost-efficient assessment of driving-related risk factors in older drivers. Method: : Seventy-four older drivers aged ≥65 years ( M = 77 years) recruited from the general population were included in this prospective observational study. Receiver operating characteristic curve (ROC) and hierarchical logistic regression analyses were utilized to examine whether the SAFE and further evidence-based driving-related factors may allow the differentiation between fit and unfit older drivers assessed in standardized on-road driving assessments. Results: : ROC analyses revealed significant diagnostic accuracy of the number of SAFE risk factors in differentiating between fit and unfit older drivers (AUC = 0.71). A stepwise logistic regression model revealed that adding further evidence-based risk factors into the SAFE clearly improved diagnostic accuracy (AUC = 0.85). Discussion: : The current study shows that the risk assessed by the SAFE predicts on-road driving fitness in older adults. However, the results also suggest a need for a modification of the SAFE by the inclusion of additional evidence-based risk factors. With sensitivity and specificity scores of about 90 % and 75 %, this modified version may be more suitable for clinical use.